Numerical Investigation of PCM-based Thermal Energy Storage System. (May 2015) - Bellan, Selvan; Gonzalez-Aguilar, Jose; Romero, Manuel; Rahman, Muhammad M.; Goswami, D. Yogi; Stefanakos, Elias K.
Abstract: A latent thermal energy storage system, which consists of sodium nitrate filled spherical capsules in a cylindrical tank, is analyzed for concentrating solar power plant applications. The high temperature synthetic oil, Therminol 66, is used as heat transfer fluid. A numerical model is developed to investigate the behavior of the system. The developed model is validated using the reported experimental and numerical data. The influence of capsule size and the flow rate of heat transfer fluid (HTF) on the temperature distribution, fluid flow, melting and solidification of the system is studied. The natural convection effect present in the liquid region during melting is resolved by the effective thermal conductivity, which is calculated by enthalpy formulation method. The results indicated that the heat transfer rate is increased and eventually the charging/discharging time is decreased when the capsule size is decreased, or the HTF flow rate is increased.